Characteristics of abdominal vein thrombosis in children and adults - Landi, Daniel; Beckman, Michele G.; Shah, Nirmish R.; Bockenstedt, Paula; Grant, Althea M.; Heit, John A.; Key, Nigel S.; Kulkarni, Roshni; Manco-Johnson, Marilyn; Moll, Stephan; Philipp, Claire S.; Andersen, Judith C.; Ortel, Thomas L. (Thrombosis and Haemostasis, 2013)
The demographic and clinical characteristics of adults and children with lower extremity deep-vein thrombosis and/or pulmonary embolism (LE DVT/PE) may differ from those with abdominal vein thrombosis (abdominal VT). Abdominal VT can be a presenting sign of an underlying prothrombotic state, and its presence in the setting of known disease might have prognostic implications different from LE DVT/PE. This study describes clinical presentations of abdominal VT compared to LE DVT/PE in adults and children. We analysed prospec-tively-collected data from consecutive consenting patients enrolled in one of seven Centers for Disease Control and Prevention (CDC) funded Thrombosis and Hemostasis Network Centers from August 2003 to April 2011 to compare the demographic and clinical characteristics of adults and children with abdominal VT. Both adults and children with abdominal VT tended to be younger and have a lower body mass index (BMI) than those with LE DVT/PE. Of patients with abdominal V T, children were more likely to have inferior vena cava (IVC) thrombosis than adults. For adults with venous thromboembolism (VTE), relatively more women had abdominal VT than LE DVT/PE, while the proportions with LE DVT/PE and abdominal VT by sex were similar in children. Children with abdominal VT were more likely to have diagnosed inherited thrombophilia, while trauma was more common in children with LE DVT/PE. In conclusion, both children and adults with abdominal VT were younger with a lower BMI than those with LE DVT/ PE. Significant differences exist between children and adults in respect to abdominal VT compared to LE DVT/PE.Disclaimer: The findings and conclusions in this report are those of the authors and do not necessarily represent the views of the Centers for Disease Control and Prevention.
Keywords: Venous thromboembolism; deep venous thrombosis; paediatrics; abdominal vein thrombosis